Organologi dan Teknik Permainan Taratoa oleh Mardi Boangmanalu di Pakpak Bharat - Pasaribu, Kevin Leonardo; Dewi, Heristina; Sebayang, Vanesia Amelia (Jurnal Pendidikan dan Penciptaan Seni, 2025)
Taratoa is one of the traditional wind instruments owned by the Pakpak people in North Sumatra. This instrument has high cultural value and is classified as an aerophone, precisely the type of end-blown flute. Its existence reflects the rich musical tradition of the Pakpak people that needs to be studied and preserved. This research aims to examine the organological aspects of Taratoa, including the manufacturing process, materials, construction, and playing techniques. The main focus is on the practice of Mardi Boangmanalu, a traditional craft and performance art form practiced by Taratoa craftsman and player from Aornakan II Village, Pargetteng-Getteng Sengkut District, Pakpak Bharat Regency. The approach used in this research is a descriptive qualitative one, employing data collection techniques that include observation, interviews, and documentation. To identify the process of making and playing techniques, this research refers to the structural and functional theory of Susumu Khasima (1978: 174). In classifying Taratoa, the Hornbostel-Sachs (1961) theory was used.